PENERAPAN METODE PEMBELAJARAN FUN LEARNING TERHADAP HASIL BELAJAR PKN MATERI HIDUP RUKUN KELAS II SDN TELANG 2 - Chusna, Nuril Lailatul (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
This study aims to determine the effect of the fun learning method on improving the learning outcomes of second grade students in PKN subjects on living in harmony at SDN Telang 2, Kamal District, Bangkalan Regency. This type of research uses classroom action research methods which are carried out with several implementation cycles, consisting of pre-cycle stages, cycle 1 and cycle 2. The subjects of this research were class II students at SDN Telang 2 consisting of 17 students in one class. Based on the results of the research that has been done, it can be concluded that the fun learning method can affect student learning outcomes. The fun learning method can improve student learning outcomes which can be seen during the research, namely at the pre-cycle stage, cycle 1 and cycle 2. At the pre-cycle stage it can be seen that student learning outcomes are still relatively low, then in cycle 1 the fun learning method has begun to be applied but still not reach minimum completeness. In the final stage, namely cycle 2, student learning outcomes have increased for the better.